Enhancing ESL Learners’ Identity Lexico-Grammatically in Language Learning Histories Writing - Wang, Jianning; Ramakrishna, Rita Abdul Rahman; Marashdeh, Mohammed Mahmoud; Rahman, Muhammad Mushfiqur (European Publisher, 2019)
The cognitive transition of ESL learner’s role from a passive recipient to an active participant has posed a great challenge for ESL teachers to rediscover learner identity. The study of ESL learner’s identity through narratives has been far from enough. A learner identity through the self-focused reflective language learning histories (LLHs) written by ESL learners could probably well represent the learner’s experience. In this study, ESL learner identity revealed in LLHs was explored to discover how learners use personal reference and strategy of identity construction to establish the relationship with their learner group. A corpus-based quantitative approach was adopted. The corpus was composed of 36 LLHs written respectively by Japanese, Finnish and Chinese undergraduates of various disciplines. Quantitatively, the frequency of first-person pronouns “I, me, my, we, us, and our” was examined and analysed. The data shows that the ratio of singular first-person pronoun in LLH texts to sentence of LLH texts is far greater than that of plural first-person pronoun use to sentence numbers. The use of first personal references in LLHs are unanimous, regardless of their various disciplines or their social background of studying. The findings indicate that the ESL learners use specific lexico-grammatical forms such as singular first-person pronouns in LLH writing and this personal reference and strategy of identity construction enhance the learners’ identity in their university language learning community.